КЛИНИЧЕСКИЙ СЛУЧАЙ РАЗВИТИЯ ТУБЕРКУЛЕЗА ПОД МАСКОЙ ОБОСТРЕНИЯ ХРОНИЧЕСКОГО БРОНХИТА - Т. А. Руженцова (SINAPS LLC, 2015)
We provide a description of clinical case of late diagnosis of tuberculosis in 67 years old male with chronic bronchitis.